Chain Extension of Stimuli‐Responsive Polymer Brushes: A General Strategy to Overcome the Drawbacks of the "Grafting‐To" Approach. (10th June 2013) - Rauch, Sebastian; Eichhorn, Klaus‐Jochen; Kuckling, Dirk; Stamm, Manfred; Uhlmann, Petra
Abstract Stimuli‐responsive polymer brushes are smart materials for the design of bio‐interactive and responsive interfaces. The "grafting‐to" approach is a convenient preparation procedure that allows the modification of surfaces with preformed and most notably well‐defined functionalized macromolecules. However, the shortcoming of this approach is an intrinsic limitation of the grafting density, which in turn affects the stimuli‐responsive properties of the brush system. Here, a general strategy to overcome this limitation and to simultaneously improve the switching behavior of a temperature‐responsive poly(N‐isopropylacrylamide) (PNiPAAm) brush is reported. A technically simple processing step is used in combination with the thermal azide–alkyne cycloaddition to perform the chain extension of alkyne‐functionalized PNiPAAm brushes with azide‐functionalized PNiPAAm molecules.